Cadmium concentrations in Idaho wheat grain and soil. Issue 3 (7th July 2022) - Strawn, Daniel G.; Mohotti, Dinithi; Carp, Elizabeth; Liang, Xi; Chen, Jianli; Schroeder, Kurtis; Marshall, Juliet
Abstract: Current efforts to reduce the maximum allowable cadmium (Cd) concentrations in wheat ( Triticum aestivum L.) for at‐risk populations such as infants require sourcing wheat with low concentrations of Cd. Since Idaho (USA) is a major wheat supplier, there is a need to understand which varieties and locations in Idaho produce wheat containing low Cd. Therefore, the main objective of this paper is to report on a survey of total Cd concentrations in 469 wheat grain samples and 216 soil samples from several varieties and locations throughout Idaho. Total Cd concentrations in wheat grain ranged from <0.01 to 0.28 mg kg −1, varying by both wheat variety and location grown. Total soil Cd ranged from 0.450 to 1.85 mg kg −1 . Bioaccumulation factor (BAF) was calculated by dividing the grain total Cd concentration by the soil total Cd concentration and ranged from 0.05 to 0.5. The variety 'UI Sparrow' had the lowest mean BAF (0.06), and several other varieties were also relatively low. Overall, almost all wheat varieties meet European Food Safety Authority (EFSA) requirements for Cd concentration for adult consumption. However, meeting the EFSA maximum allowable limit of Cd in infant food requires planting varieties noted for low Cd uptake, like UI Sparrow, and careful selection of growing regions with the lowest total soil Cd, such as northern, central, or western Idaho. Core Ideas: Cadmium concentrations in soil and wheat grain in Idaho (USA) were surveyed. Cadmium uptake in wheat is influenced by wheat variety and soil properties. Total cadmium in Idaho wheat grain ranges from <0.01 to 0.28 mg kg −1 . Total cadmium in Idaho soils ranges from 0.45 to 1.85 mg kg −1 . Bioaccumulation factor indicates the best varieties for producing wheat containing low cadmium.